The Effect Of Consumer Motivation, Quality Perception, And Consumer Attitude To The Decision Of Purchase Of Honda Brand Motorcycle IN Lamongan district: The Effect Of Consumer Motivation, Quality Perception, And Consumer Attitude To The Decision Of Purchase Of Honda Brand Motorcycle IN Lamongan district - Zulkifli Lubis; Hendro Setiyawan; Lailiyah Mukhadiroh (Jurnal Mantik, 2019)
This study aims at how much community interest in Honda products in the city of Lamongan so that it can be formulated that attract consumers' interest in making motorcycle purchasing decisions amid increasingly fierce competition phenomena based on consumer motivation, perceived quality, and consumer attitudes. The purpose of this study was to analyze the influence of consumer motivation, perceived quality, and consumer attitudes towards motorcycle purchasing decisions. This research uses quantitative methods. Data collected by questionnaire and interview techniques. Respondents in this study were 100 people who met one of five criteria; initiator, influencer, decider, buyer, user of Honda motorbikes in Lamongan City Three hypotheses were formulated and tested using Regression Analysis. While qualitative analysis is taken from the interpretation of data by providing information and explanations. The results showed that consumer motivation, perceived quality, and consumer attitudes had a significant relationship with purchasing decisions. Consumer motivation also has a higher influence on purchasing decisions than consumers' perceived quality and attitudes.